The Dynamics of Gendered Spaces in Jokha Alharthi’s Celestial Bodies - Joseph, Jesna (New Literaria, 2023)
The interactions of human agency in the totality of space creates different social structures. Feminist Geography offers a self-reflexive analysis of regimes of power that operates in everyday life. The gendered divisions in society are responsible for creating the different patterns of spatial activity, experience and behaviour. Giving insight into a traditional Islamic society, Omani writer, JokhaAlharthi’s Celestial Bodies (2018) is a criticism against dominant ideologies and power hegemony. The paper analyses the critical relationship between gendered and spatial segmentation and challenges their supposed naturalness and validity. The unequal power relations that exist within the society produce different patterns of spatial relations with respect to access to public and private spaces. Through the theoretical framework of Feminist Geography, the paper criticises the gendered divisions of space and problematises the attempt of the enduring subjects to free themselves from the narrow space of patriarchal imagination and re-invent their lives in a space of their own.Keywords: Past and present, Timeless Humanities, Boethius, Wolfram von Eschenbach, Path through Life, Relevance of Literature, Philosophy.